Friction pair
By using a friction material composition that does not contain copper and iron metal fibers and adding trimanium tetraoxide as an inorganic friction adjustment material, the problems of surface tearing and metal blocks arise at high temperatures are solved, and higher rust removal and braking efficiency stability are achieved.
Patent Information
- Application Number
- CN202180042866.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-06-16
- Filing Date
- 2021-06-09
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2041-06-09
AI Technical Summary
The prior art is difficult to effectively suppress the problem of surface tearing and metal blocks generated at high temperatures in stainless steel disc rotors, especially when the temperature of the friction material reaches high temperatures.
A friction material composition without copper components and iron-based metal fibers is used, and trimanganese tetraoxide, which has a total amount of 1 to 6% by weight relative to the total amount of the friction material composition, is added as an inorganic friction adjustment material to suppress the generation of metal blocks on the friction surface of the disc rotor.
It effectively suppresses the tear and metal blocks on the surface of stainless steel disc rotors at high temperatures, and improves the rust removal and braking performance stability of friction materials.
Smart Images

Figure BDA0004000115030000081 
Figure BDA0004000115030000091 
Figure BDA0004000115030000092
Abstract
Description
Technical Field
[0001] The invention relates to a friction pair, in particular to a friction pair used for vehicles such as passenger cars. Background Art
[0002] Conventionally, as a friction member of a disc brake for a passenger car, a disc brake pad is used, in which a friction material is bonded to a metal base member.
[0003] In recent years, due to the demand for quiet braking, disc brake pads using a friction material called NAO material that generates less braking noise have become widely used.
[0004] The friction material of NAO material is formed by molding a friction material composition containing a binder, a fiber base material other than steel fibers such as steel fibers and / or stainless steel fibers, and a friction adjustment material. It is a friction material classified in parallel with semi-metallic friction materials and / or low-steel friction materials containing steel fibers as fiber base materials. In addition, in recent years, there are also legal regulations on the content of copper components in the United States, and friction materials containing only 5% by weight or less copper or no copper at all are generally developed.
[0005] Patent document 1 describes a friction material composition and a friction material obtained by molding the friction material composition. The friction material composition contains a fiber substrate, a friction adjusting material and a bonding material. The content of copper in the friction material composition is 0.5% by mass or less in terms of copper element. The friction adjusting material contains granular titanate obtained by granulating titanate, and the average particle size of the granular titanate is 100 to 250 μm.
[0006] Patent document 2 describes a friction material composition, which is a friction material containing a fiber base material, an inorganic filler, an organic filler and a binder, and a copper content of 0.5 mass % or less. As the inorganic filler, it contains an abrasive with an average particle size of 3 to 5 μm and an abrasive with an average particle size of 9 to 13 μm. At the same time, as the inorganic filler, it contains titanate with an average particle size of 1.5 to 4.5 μm and titanate with an average particle size of 15 to 45 μm.
[0007] As a counter-friction material for a disc brake pad having such a friction material containing almost no copper components, a cast iron disc rotor as described in Patent Document 3 is used. Such a cast iron disc rotor has low corrosion resistance and has the problem of rusting during use, so a solution is needed in the friction material.
[0008] For example, Patent Document 4 discloses a friction material comprising a bonding material, a friction adjusting material and a fiber substrate, which has improved rust removal properties on the abrasive material by not containing a copper component but containing 10 to 20 volume % of at least one titanate compound having a plurality of protrusions and 1 to 20 volume % of biosoluble inorganic fibers.
[0009] However, as the installation of regenerative brakes is promoted due to the popularization of electric vehicles and hybrid vehicles, the braking load of the friction material of the conventional hydraulic brake is reduced, so even if the technology of Patent Document 4 is used, there is a problem that sufficient rust removal performance cannot be obtained.
[0010] Therefore, disc rotors made of stainless steel having excellent rust resistance are increasingly being used.
[0011] Patent Document 5 discloses a four-wheel disc rotor made of a stainless steel plate having a martensitic structure or a mixed structure of a martensitic phase and a ferrite phase.
[0012] Patent Document 6 describes a disc rotor for an automobile having a structure containing martensite and carbonitride and optionally containing ferrite.
[0013] Patent Document 7 describes a disc rotor for an automobile made of a stainless steel plate, wherein the stainless steel plate is characterized by containing, by mass%, C: 0.005-0.100%, Si: 0.01-1.00%, Mn: 0.010-3.00%, P: 0.040% or less, S: 0.0100% or less, Cr: 10.0-14.0%, N: 0.005-0.100%, V: 0.03-0.30%, Al: 0.001-0.050%, B: 0.0002-0.0050%, Ni: 0-2.00%, Cu: 0-2.00%, Mo: 0~1.00%, W: 0~1.00%, Ti: 0~0.40%, Nb: 0~0.40%, Zr: 0~0.40%, Co: 0~0.400%, Sn: 0~0.40%, REM: 0~0.050% or less, Mg: 0~0.0100%, Ca: 0~0.0100%, Sb: 0~0.50%, Ta: 0~0.3000%, Hf: 0~0.3000%, Ga: 0~0.1000%, the remainder is composed of Fe and impurities, the metal structure is composed of ferrite phase, and 10~50 / 100μm are used in any cross section. 2 Carbonitrides having a diameter equivalent to a circle of 0.3 μm or more are present.
[0014] In such a background, there is a need for a friction material made of a friction material composition that does not contain a copper component and is suitable for a stainless steel disc rotor having excellent rust resistance. However, it is known that when a stainless steel disc rotor having a large elongation at break and easily plastically deformed reaches a high temperature, the surface of the disc rotor is likely to tear and metal lumps derived from the components of the disc rotor are generated on the surface of the disc rotor.
[0015] Prior art literature
[0016] Patent Literature
[0017] Patent Document 1: Japanese Patent Application Publication No. 2017-57312
[0018] Patent Document 2: Japanese Patent Application Publication No. 2018-162385
[0019] Patent Document 3: Japanese Patent Application Laid-Open No. 2-134425
[0020] Patent Document 4: Japanese Patent Application Publication No. 2017-149971
[0021] Patent Document 5: Japanese Patent Application Publication No. 2016-117925
[0022] Patent Document 6: Japanese Patent Application Publication No. 2019-173086
[0023] Patent Document 7: Japanese Patent Application Publication No. 2019-178419 Summary of the invention
[0024] Problems to be solved by the invention
[0025] The object of the present invention is to provide a friction pair capable of suppressing the generation of metal blocks on the friction surface of a disc rotor, the friction pair comprising a disc brake pad having a friction material composed of a friction material composition, and a disc rotor made of stainless steel, the friction material composition containing a binder, a fiber substrate, a friction adjusting material, and not containing a copper component and an iron-based metal fiber.
[0026] Means used to solve problems
[0027] As a result of intensive research by the inventors of the present invention, a friction pair has been discovered, comprising a disc brake pad having a friction material composed of a friction material composition, and a disc rotor made of stainless steel, wherein the friction material composition contains a binder, a fiber substrate, a friction adjusting material, and does not contain a copper component and iron-based metal fibers, and the friction material composition does not contain metal fibers other than iron-based metal fibers. By using a friction material composition containing 1 to 6 weight percent of trimanganese tetraoxide as an inorganic friction adjusting material relative to the total amount of the friction material composition, a friction pair capable of suppressing the generation of metal blocks on the friction surface of the disc rotor can be obtained, thereby completing the present invention.
[0028] The present invention relates to a friction pair, which includes a disc brake pad having a friction material composed of a friction material composition, and a disc rotor made of stainless steel. The friction material composition contains a bonding material, a fiber substrate, and a friction adjusting material, and does not contain a copper component and an iron-based metal fiber. The present invention is based on the following technology.
[0029] (1) A friction pair comprising a disc brake pad having a friction material composed of a friction material composition, and a disc rotor made of stainless steel, wherein the friction material composition contains a binder, a fiber substrate, and a friction adjusting material and does not contain a copper component and iron-based metal fibers, wherein the friction material composition does not contain metal fibers other than the iron-based metal fibers and contains 1 to 6% by weight of trimanganese tetraoxide as an inorganic friction adjusting material based on the total weight of the friction material composition.
[0030] (2) The friction pair according to (1), wherein the friction material composition contains 1 to 10 wt % of graphite as a lubricant relative to the total weight of the friction material composition.
[0031] Effects of the Invention
[0032] According to the present invention, a friction pair can be provided, which can suppress the generation of metal blocks on the friction surface of a disc rotor, and includes a disc brake pad having a friction material composed of a friction material composition, and a disc rotor made of stainless steel, wherein the friction material composition contains a binder, a fiber substrate, and a friction adjusting material, and does not contain a copper component and an iron-based metal fiber. DETAILED DESCRIPTION
[0033] Compared with cast iron disc rotors, stainless steel disc rotors have lower thermal conductivity and thermal diffusivity. In addition, stainless steel has a slightly higher specific gravity than cast iron, but slightly higher strength. Therefore, assuming that a stainless steel disc rotor has the same weight and strength as a cast iron disc rotor, the thickness of the disc rotor will be designed to be thinner. As a result, the heat capacity of the disc rotor becomes smaller, the disc rotor is more likely to store heat, and the temperature of the friction material is more likely to reach a high temperature.
[0034] In addition, stainless steel has a large elongation at break and is easily plastically deformed. Therefore, when the disc rotor reaches a high temperature, the surface of the disc rotor is easily torn, and there is a problem that metal lumps derived from the components of the disc rotor are generated on the surface of the disc rotor.
[0035] The metal chunks generated on the surface of the disc rotor can cause abnormal wear of the friction material, so a technology to suppress the generation of the metal chunks is required.
[0036] Therefore, the present invention relates to a friction pair, comprising a disc brake pad having a friction material made of a friction material composition and a disc rotor made of stainless steel, wherein the friction material composition contains a binder, a fiber substrate, a friction adjusting material, and does not contain a copper component and iron-based metal fibers, and uses a friction material composition that does not contain metal fibers other than iron-based metal fibers and contains 1 to 6 weight % of trimanganese tetraoxide as an inorganic friction adjusting material relative to the total amount of the friction material composition.
[0037] The trimanganese tetraoxide is reduced to manganese by friction. Since manganese has the effect of improving the toughness of stainless steel, it is difficult for the disc rotor surface to be torn, and the generation of metal blocks on the friction surface of the disc rotor is suppressed.
[0038] In addition, by adding 1 to 10 wt % of graphite such as artificial graphite, natural graphite, and graphite flake powder relative to the total weight of the friction material composition, the reduction of trimanganese tetraoxide is promoted, thereby improving the effect of suppressing the generation of metal blocks on the friction surface of the disc rotor.
[0039] <Friction material composition>
[0040] The friction material used in the friction pair of the present invention is composed of a friction material composition, which contains, in addition to the trimanganese tetraoxide and graphite, a binder material, a fiber base material and a friction adjusting material commonly used in friction materials.
[0041] As the binding material, there can be listed straight-chain phenolic resin, acrylic rubber modified phenolic resin, silicone rubber modified phenolic resin, nitrile rubber modified phenolic resin, cashew nut oil modified phenolic resin, aralkyl modified phenolic resin (phenol aralkyl resin) obtained by reacting phenols, aralkyl ethers and aldehydes, acrylic rubber dispersed phenolic resin, silicone rubber dispersed phenolic resin, fluoropolymer dispersed phenolic resin and other binding materials commonly used in friction materials. They can be used alone or in combination of two or more.
[0042] The content of the binder is preferably 4 to 9 wt %, more preferably 6 to 8 wt %, based on the total amount of the friction material composition.
[0043] Examples of the fiber substrate include organic fibers commonly used in friction materials, such as aramid fibers, acrylic fibers, cellulose fibers, and polyparaphenylenebenzobisoxazole fibers. These fibers may be used alone or in combination of two or more.
[0044] The content of the fiber base material is preferably 1 to 5% by weight, more preferably 2 to 4% by weight, based on the total amount of the friction material composition.
[0045] As the friction adjusting material, a lubricating material, an inorganic friction adjusting material, and an organic friction adjusting material can be used.
[0046] As lubricating materials, in addition to the above-mentioned graphite, there can be listed carbonaceous lubricating materials such as petroleum coke, coal coke, elastic graphitized carbon, oxidized polyacrylonitrile fiber crushed powder, and metal sulfide lubricating materials such as molybdenum disulfide, zinc sulfide, tin sulfide, and composite metal sulfide. They can be used alone or in combination of two or more.
[0047] The total content of the lubricating material and the graphite is preferably 10 to 18 wt %, more preferably 11 to 16 wt %, based on the total amount of the friction material composition.
[0048] Inorganic friction adjustment materials include, in addition to the above-mentioned manganese manganese tetroxide, calcium hydroxide, calcium carbonate, barium sulfate, talc, dolomite, zeolite, ferrosoferric oxide, calcium silicate hydrate, magnesium oxide, silicon dioxide, zirconium oxide, zirconium silicate, γ-alumina, α-alumina, silicon carbide, columnar titanates, plate-like titanates, granular titanates, flaky titanates, titanates of amorphous shapes with multiple protrusions (titanates include potassium titanate, potassium lithium titanate, potassium magnesium titanate, sodium titanate, etc.), wollastonite, sepiolite, basalt fiber, glass fiber, biosoluble ceramic fiber, rock wool, etc. They can be used alone or in combination of two or more.
[0049] The total content of the inorganic friction modifier and the trimanganese tetraoxide is preferably 60 to 82 wt %, more preferably 65 to 76 wt %, based on the total amount of the friction material composition.
[0050] As organic friction adjusting materials, there can be listed cashew nut oil friction powder, tire tread rubber powder, polytetrafluoroethylene powder, or vulcanized rubber powder or unvulcanized rubber powder such as acrylic rubber, isoprene rubber, nitrile rubber, styrene-butadiene rubber, butyl rubber, silicone rubber, etc., which are organic friction adjusting materials commonly used in friction materials. They can be used alone or in combination of two or more.
[0051] The content of the organic friction adjusting material is preferably 3 to 8% by weight, more preferably 5 to 7% by weight, based on the total amount of the friction material composition.
[0052] <Method for manufacturing disc brake pad>
[0053] The disc brake pad according to the present invention is generally manufactured by the following process:
[0054] A mixing process of uniformly mixing the friction material composition (friction material raw material) prepared in a predetermined amount using a mixer to obtain a friction material raw material mixture,
[0055] The obtained friction material raw material mixture is superimposed on a back plate which has been cleaned, surface treated and coated with an adhesive material in advance, and then placed in a thermoforming mold for heat and pressure molding.
[0056] The obtained molded product is heated to complete the heat treatment process of the curing reaction of the adhesive material.
[0057] A coating process that uses spraying or electrostatic powder coating to apply the paint.
[0058] The coating baking process of the baking paint, and
[0059] A grinding process that uses a rotating grindstone to form a friction surface.
[0060] After the heating and pressurizing step, the coating step, the heat treatment step also serving as the coating baking step, and the polishing step may be sequentially performed for production.
[0061] If necessary, before the heating and pressing process, the following can be carried out:
[0062] The granulation process of granulating the friction material raw material mixture,
[0063] The kneading process of kneading the friction material raw material mixture,
[0064] A preforming step of placing the friction material raw material mixture or the granulated product obtained in the granulating step and the kneaded product obtained in the kneading step into a preforming die to form a preform,
[0065] The scorching step may be performed after the heating and pressure molding step.
[0066] <Stainless steel disc rotor>
[0067] As the stainless steel disk rotor, for example, a disk rotor made of martensitic stainless steel or ferritic stainless steel can be used.
[0068] Example
[0069] The present invention will be specifically described below with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples.
[0070] [Methods for producing friction materials of Examples 1 to 11 and Comparative Examples 1 and 2]
[0071] The friction material composition having the composition shown in Table 1 was placed in Mix in a mixer for 5 minutes to obtain a friction composition mixture. Pressurize the friction material composition mixture at 30 MPa for 10 seconds in a molding mold to obtain a friction material preform. Place the friction material preform on a steel back plate that has been finely cleaned, surface treated, and coated with an adhesive material in advance, and mold it in a hot molding mold at a molding temperature of 150°C and a molding pressure of 40 MPa for 10 minutes to obtain a friction material mold. After heat treating (post-curing) the friction material mold at 200°C for 5 hours, grind it to form a friction surface and produce a disc brake pad for a passenger car.
[0072] Table 1
[0073]
[0074] Furthermore, the friction material of the disc brake pad was cut into a size of 25 mm×15 mm×15 mm to obtain test pieces of Examples 1 to 11 and Comparative Examples 1 and 2.
[0075] Table 2 shows the "test conditions", "material of the friction material", "evaluation items" and "evaluation criteria" used when these test pieces were used to detect the "generation of metal blocks on the friction surface of the disc rotor" and the "stability of the braking performance".
[0076] Table 2
[0077]
[0078] Table 3 shows the evaluation results of “generation of metal masses on the friction surface of the disc rotor” and “stability of braking performance” shown in Table 2, which were performed for each Example and each Comparative Example.
[0079] Table 3
[0080]
[0081] It can be seen from Table 3 that the friction material that meets the conditions of the present invention can suppress the generation of metal blocks on the friction surface of the disc rotor, and its braking performance stability is also high.
[0082] Industrial Applicability
[0083] According to the present invention, a friction pair can be provided, which can suppress the generation of metal blocks on the friction surface of a disc rotor and has high braking performance stability. The friction pair includes a disc brake pad having a friction material composed of a friction material composition, and a stainless steel disc rotor. The friction material composition contains a bonding material, a fiber substrate, and a friction adjusting material, and does not contain copper components and iron-based metal fibers. The friction pair has extremely high practical value.
Claims
1. A friction pair comprising a disc brake pad having a friction material composed of a friction material composition, and a disc rotor made of stainless steel, wherein the friction material composition contains a binder, a fiber substrate made of organic fibers, and a friction adjusting material, and does not contain a copper component and an iron-based metal fiber, characterized in that: The friction material composition does not contain metal fibers other than iron-based metal fibers, and contains trimanganese tetraoxide as an inorganic friction modifier in an amount of 1 to 6 wt % relative to the total amount of the friction material composition.
2. The friction pair according to claim 1, characterized in that: The friction material composition contains 1 to 10 wt % of graphite as a lubricant relative to the total weight of the friction material composition.
Citation Information
Patent Citations
Disk rotor material
JP1990134425A
Four wheel stainless steel disk brake rotor and method for manufacturing the same
JP2016117925A
Friction material composition and friction material
JP2017057312A
Friction material
JP2017149971A
Friction material composition, and friction material and friction member using the friction material composition
JP2018162385A